ISOLASI GENISTEIN DARI TEMPE SECARA KROMATOGRAFI - Wuryani Wuryani (Research Center for Chemistry - LIPI, 1994)
The presence of genisteln in tempe (fermented soybean) could be detected by using various chromatographic techniques, such as Thin-Layer, Column and High Pressure Liquid Chromatography. In this experiment, TLC was chosen for the isolation and purification of genistein from tempe. Spectrophotometry, Mass Spectrometry, spraying with chromogenic reagents and hydro- lysis were carried out for identifying genistein. Quantification was carried out spectrophotometrlcally and it was shown that the laboratory prepared tempe (l00 g) contained 13.80 mg ofgenisteln.